Old World Diamond-Flower Biology and Management in Turf - Darcy E. P. Telenko; Barry J. Brecke; Ramon Leon; J. Bryan Unruh (EDIS)
Old world diamond-flower is a smooth, spreading summer annual. It has branched stems with opposite, narrow leaves. Flowers are white, usually with two or more on long stalks extending from the tip of a common long stalk. Flowers occur from midsummer until frost. Reproduction occurs by seed. Found in moist areas, especially areas that have been disturbed. This 2-page fact sheet was written by Darcy E. P. Telenko, Barry J. Brecke, Ramon Leon, and J. Bryan Unruh, and published by the UF Department of Environmental Horticulture, December 2013.